A Search for Piroplasmids and Spirochetes in Threatened Pudu (Pudu Puda) and Associated Ticks from Southern Chile Unveils a Novel Babesia Sp. and a Variant of Borrelia Chilensis - Moreira-Arce, D (John Wiley and Sons Inc, 2022)
Cervids are important hosts for ticks and although they are refractory to some tick-borne agents such as Borrelia, they do act as reservoirs for others such as Babesia. Babesia and Borrelia are commonly transmitted by Ixodes spp. associated with deer, and most of the knowledge on their biological cycles comes from northern latitudes of the globe. In this study, we performed genetic screenings to detect tick-borne agents in blood and Ixodes stilesi ticks collected from an insular population of threatened pudu (Pudu puda), a pygmy deer species that inhabits temperate rainforests of southern South America. Inferred by phylogenetic analyses for 18S rRNA, COI and cytb genes, our results unveiled a novel genospecies of Babesia (Babesia sp. pudui) genetically related to Babesia odocoilei, a species that infects Odocoileus virginianus deer in North America. Although blood of the deer was negative for Borrelia infection, multilocus sequencing typing performed in one I. stilesi tick revealed the occurrence of a novel genetic variant of Borrelia chilensis, differing 0.93% and 0.18% in flaB and pepX genes with the type of strain for the species, respectively. Such a genetic divergence could be the result of thousands of years of isolation because of recent glaciation events that separated pudus and their tick populations at Chiloé Island approximately 437,000 years ago. The finding of a Babesia sp. has no precedents for wild and domestic ungulates in Chile and shows a novel piroplasmid that must be considered now on in rehabilitation centres and zoos that attend pudu deer. Further research is now necessary to confirm pathogenic roles. © 2022 Wiley-VCH GmbH.